(untitled) (Epidemiology, Biostatistics, and Public Health, 2022)
Background: The importance of health insurance to individual and society at large cannot be overemphasized. It plays a critical role through enabling access to health care services and cushions the individual from catastrophic treatment costs. This study assessed the demographic and socioeconomic determinants of maternal health insurance coverage in Zambia. Methods: The study analysed the data from the 2013-14 Zambia Demographic and Health Survey (ZDHS) using univariate, bivariate, binary logistic regression analyses to examine the relationship between demographic and socioeconomic and maternal health insurance coverage in Zambia. Results: The findings indicate that a very low proportion of the women(3%) have health insurance coverage in Zambia. The study also found that being married, access to media, higher age category, higher education level, being employed have a positive influence on health insurance coverage while province of residence and type of place of residence are negatively associated with health insurance coverage among women in Zambia. Conclusions:The study concludes that health insurance among women in Zambia is associated with marital status, access to media, age, education level, employed status, province of residence and type of place of residence. Given these findings, the study recommends that health insurance providers should tailor their health insurance packages not only to the needs of the employed but the unemployed, the younger age groups, the informal sector and those in the rural areas